Fluid-To-Fluid Interaction of Rhamnolipid Biosurfactants with Divalent Ions: Investigation of Interfacial Tension and Emulsion Viscosity - Hariyadi; Cahyaningtyas, Ndaru; Nugraha, Fanata Yudha; Larasati, Karina; Fatahillah, Azhar Faari; Astuti, Dian Indri (Scientific Contributions Oil and Gas, 2026)
Rhamnolipid biosurfactants derived from microbial sources have gain substantial interest as environmentally sustainable alternatives to synthetic surfactants, particularly in the realm of Microbial Enhanced Oil Recovery (MEOR). Their biodegradability, low toxicity, and effectiveness under extreme conditions make them ideal candidates for improving oil displacement in reservoir. However, the presence of divalent ions, specifically calcium (Ca²⁺) and magnesium (Mg²⁺), which are abundant in reservoir brine, can significantly affect the performance of these biosurfactants. This research investigates the influence of Ca²⁺ and Mg²⁺ ions on the phase behavior, stability, and interfacial properties of rhamnolipid-based microemulsion systems, which play a critical role in MEOR processes. A series of experiments was conducted to analyze the impact of varying concentrations of Ca²⁺ and Mg²⁺ ions on rhamnolipid microemulsions. The study evaluated phase transitions, stability, and microstructural characteristics of emulsions using a spinning drop tensiometer to measure interfacial tension (IFT) and rheological analysis to determine viscosity. The results demonstrate that both Ca²⁺ and Mg²⁺ ions influence the optimal salinity conditions required for microemulsion stability, with their presence causing shifts in the phase boundaries. Notably, Ca²⁺ ions exert a more pronounced effect on phase stability compared to Mg²⁺, leading to increased IFT and viscosity at higher concentrations. These findings further elucidates the crucial role of divalent ions in governing the stability and functionality of biosurfactant systems under reservoir conditions and highlight the importance of controlling ion concentrations to achieve efficient MEOR applications. Overall, this research provide valuable insight for optimizing the formulation of rhamnolipid-based systems to enhance oil recovery performance while mitigating the adverse effects of high divalent ion content in brine. The research contributes to ongoing efforts to improve biosurfactant efficacy, offering a pathway toward refining MEOR strategies and advancing sustainable oil recovery technologies.